The Effectiveness of Telang Flower Extract Sitz Bath on Healing Perineal Wounds in Postpartum Mothers - Mika Oktarina; Anisah Tifani Maulidyanti (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Perineal wounds are a common problem experienced by postpartum mothers. Improper treatment may delay wound healing, increase the risk of infection, and reduce maternal comfort. One non-pharmacological intervention that may accelerate wound healing is a sitz bath with telang flower extract (Clitoria ternatea), which contains flavonoids, anthocyanins, and tannins with anti-inflammatory, antioxidant, and astringent properties. The purpose of this study was to determine the effect of perineal wound care using sitz bath method with Telang flower extract on perineal wound healing in postpartum women at Mutiara Agma Pratama Clinic, Bengkulu Town. Method: This study used a quasi-experimental design with a pre-post-test control group approach. A total of 26 respondents were selected using purposive sampling, consisting of 13 respondents in the intervention group and 13 respondents in the control group. Data were collected using the REEDA scale observation sheet. Statistical analysis included the Shapiro-Wilk normality test, Levene’s Test for homogeneity, Paired Samples T-Test, and Independent Samples T-Test. Result: The results showed a decrease in the average REEDA score in the intervention group from 8.46 to 1.38 (difference = 7.077; p = 0.000), while the control group decreased from 8.62 to 4.46 (difference = 4.154; p = 0.000). The Independent Samples T-Test revealed a significant difference in posttest REEDA scores between the intervention and control groups (p = 0.000). The intervention group had a lower average REEDA score, indicating better perineal wound healing. Conclusion: The sitz bath method with telang flower extract was proven effective in accelerating perineal wound healing in postpartum mothers. This intervention can be considered as an alternative non-pharmacological perineal wound care method in health facilities and may also be applied as self-care at home under the guidance of health workers.